Analisis Akuntansi Aset Tetap Berdasarkan PSAP No. 07 pada Disperindag Provinsi Sulawesi Utara - Agrita Dila Pomo; Fanesa Isalia Minanda Syaefudin; Belthasar Trito Siahaan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the application of fixed asset accounting based on the Government Accounting Standards Statement (PSAP) Number 07 at the Department of Industry and Trade (Disperindag) of North Sulawesi Province. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation of the financial statements and fixed asset records of the entity, and then analyzed using qualitative descriptive analysis. The results show that the application of fixed asset accounting at the North Sulawesi Provincial Disperindag covers recognition, measurement, depreciation, termination and disposal, as well as disclosure of fixed assets. Fixed assets are valued using the historical cost principle. Of the 12 components of fixed asset presentation regulated in PSAP Number 07, 11 components have been applied appropriately, while the depreciation component has not been fully implemented due to the absence of technical guidelines for depreciation per type of fixed asset. This study concludes that the application of fixed asset accounting at the North Sulawesi Provincial Disperindag is generally in accordance with PSAP Number 07, but still requires improvement in terms of depreciation and completeness of documentation